Effects of lateral hydrological connectivity on the relative abundance of water frogs (Pelophylax spp.) and common toads (Bufo bufo) using eDNA surveys - Boglárka Mészáros; Andrea Funk; Thomas Hein; Lukas Landler; Paul Meulenbroek; Didier Pont; Alice Valentini; Dénes Schmera; István Czeglédi; Tibor Erős (Hydrobiologia, 2026)
Riverine floodplains support diverse amphibian communities by providing essential habitats, with lateral hydrological connectivity (LHC or hydrology) determining local environmental conditions. Our study evaluated the direct and indirect effects of LHC on the two most abundant species in a riverine floodplain. We assessed the relative abundance of water frogs ( Pelophylax spp.) and common toads ( Bufo bufo ) using eDNA surveys at 30 sites along an LHC gradient in the Danube River floodplain. We examined the habitat structure, vegetation cover, and the physical and chemical characteristics of waterbodies. Structural equation models (SEM) were used to explore LHC’s direct and indirect effects, mediated by these environmental factors. Results showed that LHC did not directly influence Pelophylax spp. and B. bufo abundance but affected them indirectly and species specifically through environmental drivers. Hydrology negatively and indirectly impacted Pelophylax spp. through vegetation cover and the physical and chemical properties of waterbodies. B. bufo was affected in a similar way but primarily through habitat structure. Our findings highlight the importance of understanding species-specific responses to lateral hydrological connectivity in dynamic environments, as river regulation altering LHC can differentially impact amphibian species in riverine floodplains.